Numerical analysis of viscoelastic process-induced residual distortions during manufacturing and post-curing. (April 2018) - Benavente, Maria; Marcin, Lionel; Courtois, Alice; Lévesque, Martin; Ruiz, Edu
Abstract: Degree of cure- and temperature-dependent elastic and viscoelastic models were implemented into ABAQUS to compute the geometrical distortion developed during the RTM manufacturing and post-curing of asymmetric plates and corner shaped parts. Comparisons between the predicted and experimental geometrical distortion for an asymmetric plate reinforced with 3D interlock woven fabric are presented. The results showed that the parts can experience creep behavior when submitted to free-standing post-curing, increasing the total geometrical distortion up to 30%, depending on post-curing cycle and part geometry. The numerical results of this work demonstrate that a temperature-dependent viscoelastic model is needed to accurately predict the geometrical distortion evolution developed during cure cycles where post-curing processes are involved.